Sinergitas DJBC dan Kepolisian dalam Memberantas Penyelundupan Rokok Ilegal : Perspektif Hukum Islam - Larissa, Dea (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
Illegal cigarette smuggling often occurs in Makassar City. In fact, most of the source of state revenue comes from the Tobacco Product Excise. Recently, on March 14, 2022, Customs and Excise found 1,099,800 cigarettes illegally. Illegal cigarette smuggling has clearly harmed the state and society. The purpose of this study was to determine the modus operandi of the perpetrators and the synergy between the Direktorat Jenderal Bea dan Cukai (DJBC) and the Indonesian National Police in eradicating illegal cigarette smuggling. This research is a qualitative-normative research with a case study approach. The results of the study show that the modus operandi of illegal cigarette smuggling is very diverse. However, the modus operandi of illegal cigarette smuggling that occurred on March 11-19 2022 in Makassar was using an expedition service. To eradicate illegal cigarette smuggling, DJBC has built a synergistic partnership with the Indonesian National Police through cooperation in supervision, investigation, investigation, and enforcement operations. Another form of synergy carried out by DJBC is conducting official visits as a form of appreciation for cooperation and for sustainable synergy.